2020
DOI: 10.1088/1361-6560/abb02c
|View full text |Cite
|
Sign up to set email alerts
|

Truncation compensation and metallic dental implant artefact reduction in PET/MRI attenuation correction using deep learning-based object completion

Abstract: The susceptibility of MRI to metallic objects leads to void MR signal and missing information around metallic implants. In addition, body truncation occurs in MR imaging for large patients who exceed the transaxial field-of-view of the scanner. Body truncation and metal artefacts translate to incomplete MRI-derived attenuation correction (AC) maps, consequently resulting in large quantification errors in PET imaging. In this work, we propose a deep learning-based approach to predict the missing information/reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Any issues or image artefacts affecting CT images would be reflected in the attenuationcorrected PET images, potentially leading to misdiagnosis and/or quantitative errors [4,5]. Moreover, CT images commonly serve as standard of reference for the evaluation of MRI-guided attenuation correction [6][7][8] and MRI-only treatment planning in radiation oncology [9].…”
Section: Introductionmentioning
confidence: 99%
“…Any issues or image artefacts affecting CT images would be reflected in the attenuationcorrected PET images, potentially leading to misdiagnosis and/or quantitative errors [4,5]. Moreover, CT images commonly serve as standard of reference for the evaluation of MRI-guided attenuation correction [6][7][8] and MRI-only treatment planning in radiation oncology [9].…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies showed that the spin-echo (SE) sequence signi cantly reduces the susceptibility artifact compared with the gradient-echo (GRE) sequence, yet, this still did not meet the expected standards. Furthermore, advances in MR sequence (e.g., VAT, SEMAC, MAVRIC, UTE) and serious deep learn-based methods now allow signi cantly improved image quality in the presence of ferromagnetic materials [10][11][12][13][14][15] . The PROPELLER sequence has the advantages of mature technology, imaging easily and high signal-to-noise ratio, and has been widely applied in clinical MR imaging to reduce motion artifacts [17][18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, various deep learning-based approaches were developed to reduce metal artifacts, improve image quality, and even predict the missing information/regions in MR images affected by metal artifacts [13][14][15] . However, the clinical uses of these methods were restricted due to safety and quality control issues, as well as complex principles and higher demand for MRI equipment in hardware and software 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In Atlasbased algorithms [80,81], pairs of co-registered MR and CT images (considered as template or atlas) are aligned to the target MR image to generate a continuous attenuation map. The main disadvantage of atlasbased algorithms is the high dependence on the atlas dataset and suboptimal performance for subjects presenting with anatomical abnormalities [82,83].…”
Section: Quantitative Imagingmentioning
confidence: 99%